e-Learning: Practices Among Undergraduates of a Medical College of Khyber Pakhtunkhwa - Mohammad Idris; Waqar Ali; Bakhtawar Obaid; Akash Kumar; Eemaz Nathaniel; Sarah Rahim; Maria Islam; Hajra Yousafzai (ziauddin University, 2024)
Background: Information technology (IT) is a new way of teaching and learning. One of the promising media of information technology is e-Learning, which is used to enhance knowledge and skills among users. A student gains better and deep knowledge through a useful tool. This survey aimed to determine practices among medical students for e-Learning. Methods: This cross-sectional survey was conducted on 184 students amongst the 500 students currently enrolled in medical college. Data was collected using questionnaires and were analyzed through SPSS version 22. Chi-square was used for qualitative values. Results: Majority 90.80% (n=167) students were aware of e-Learning and were statistically high in ﬁrst year students (p-value: 0.018). The student did not show statistically signiﬁcant results for content learned through e-Learning with a p-value of 0.063. Different resources were used for e-Learning in which videos had the highest percentage (87.60%) and audios were used as the least resource for e-Learning (29.20%). Daily, 56% of the students use e-Learning for 1 hour or less and only 3% of the students used it for more than 4 hours. Conclusion: Majority of undergraduate medical students were aware of the use of e-Learning and most of them preferred e-Learning for their course work and studies showing a signiﬁcant increase in understanding and use, compared to studies conducted earlier. Participants found e-Learning useful and effective tool in increasing knowledge and understanding of their subject. Keywords: e-Learning; Practices; Students.